An Assessment Of The Role Of Government Agencies In Public-private Partnerships In Housing Delivery In Nigeria - Ibem, Eziyi Offia (Penerbit Universiti Sains Malaysia, 2010)
Nigeria faces a tremendous shortfall in housing provisions, especially in its urban areas. Consequently, Public-Private Partnership in housing provisions has been adopted as a means of addressing this problem. Several previous studies have focused on the role of government agencies in the governmentprovider approach to housing, but adequate attention has not been given to the role of government agencies in Public-Private Partnerships in housing. This paper attempts to fill this gap in literature by examining the role of government agencies in Public-Private Partnerships in housing. A study of thirteen government agencies in six selected Nigerian cities was undertaken. The findings indicate that though the agencies tended to focus on the provision of access to land and the regulatory framework for housing development, the majority of Nigerians have not benefited from this arrangement. The paper recommends that government agencies should also be involved in providing basic amenities and subsidies to ensure that Public-Private Partnership housing serves the interest of most Nigerians.